Sea-level rise in Hai Phong coastal area (Vietnam) and its response to ENSO - evidence from tide gauge measurement of 1960-2020 - Nguyen Minh, Hai; Ouillon, Sylvain; Vu Duy, Vinh (Vietnam Journal of Earth Sciences, 2022)
The Hai Phong coastal area (Northwest of the Vietnam East Sea) is prosperous and densely populated, but it is also a place that is considered likely to be severely affected by sea-level rise. Based on the tide gauge measurement data at Hon Dau station during 1960-2020, the sea-level rise trends were analyzed and linked to the El Niño Southern Oscillation (ENSO). The analyses were carried out separately for the whole period (1960-2020) and for the last 19 years (2002-2020) by the Mann-Kendall test and Sen’s slope estimator. The Empirical Mode Decomposition method was used to identify the role of ENSO on the water level variability. The results showed a significant sea-level rise trend with a 95% confidence level. The average annual rates of sea-level were 3.56 mm/year and 7.78 mm/year over the periods 1960-2020 and 2002-2020, respectively, indicating a sea-level rise of about 21.4 cm over 60 years and a significant acceleration in sea-level rise recently (14.7 cm over the last 19 years). Sea-level that rose during El Niño events and declined during La Niña, related to ENSO with cycles of 2 and 6.1 years. From 1960 to 2020, ENSO events took four months to impact the sea-level in the Hai Phong coastal area, causing sea-level variability within -3.7 to 7.2 cm over 1972-2020.